Bio 2010 : transforming undergraduate education for future research biologists / National Research Council (U.S.). Committee on Undergraduate Biology Education to Prepare Research Scientists for the 21st Century.
"This new book provides a blueprint for bringing undergraduate biology education up to the speed of today's research fast tracks. It includes recommendations for teaching the next generation of life science investigators, through: building a strong interdisciplinary curriculum that integrates physical science, information technology, and mathematics with the life sciences; decreasing the administrative and financial